Research on high-precision large-aperture laser differential confocal-interferometric optical element multi-parameter measurement method - Weiqian Zhao; Liang Tang; Shuai Yang; Lirong Qiu (Light: Advanced Manufacturing)
To fulfill the requirements of high-precision common baseline measurement for multiple parameters, such as surface profiling and the curvature radius of large-aperture optical elements on the same instrument, this paper proposes a research on a high-precision large-aperture laser differential confocal-interferometric measurement method. This method is based on the principle of laser differential confocal combined with interferometry. It utilizes a Galilean double-reflection collimation system to generate well large-aperture collimated beams and employs mechanical phase-shifting technology for large-aperture and heavy-load reference lenses to overcome the flaws of existing large-aperture wavelength-tuning phase shifting technology in theory, thus achieving high-precision and high-stable phase-shifting interference in large-aperture surface profiling measurements. By utilizing the laser differential confocal method with anti-scattering and anti-interference properties, high-precision common baseline measurements are achieved for the multiple-parameter of optical elements such as ultra-long focal lengths and ultra-large curvature radii. The measurements of large-aperture surface profiles, the mean PV was 46.0 nm. For the ultra-long focal length, the relative standard deviation was 0.019%, whereas for the ultra-large curvature radius, the relative standard deviation was 0.0036%. This method enables high-precision, high-stable, and high-efficient common baseline measurements for the multiple parameters of optical elements with large, medium, and small apertures thereby providing an effective technical approach for improving the detection and machining precision of optical elements.